EFFECTS OF COPPER WIRE ADDED WICK ON THE PERFORMANCE OF WASTE COOOKING OIL STOVE - Muhammad Agus Windra; Tamrin .; Agus Haryanto (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2013)
This study aimed to determine the effect of copper wires addition to the cloth wick on the performance of stove fueled by waste cooking oil. The study was divided into two stages.  First, is to test the capillarity of wick at different copper wires addition by observing flame quality, capillary height, and flaming period. Second, is to design a stove based on the results obtained in the first stage and to test performance of the stove in boiling water. Parameters to be observed include boiling time, rate of fuel consumption, and thermal efficiency. The results showed that the addition of copper wires increase the wick’s capillarity characterized by increasing absorption of the used cooking oil. Wick with a composition of  20 % copper wires and 80 % cloth produced the best capillarity (7.5 cm height). Waste cooking oil stove was capable to boil 3 kg of water in 15 minutes with a fuel consumption rate of 0.1275 kg/hour. The stove has a thermal efficiency of 33,33 %. Keywords: Stove, Waste cooking oil, Copper wire added wick.